(untitled) (The Batuk, 2025)
This study investigated the influence of key behavioral biases; overconfidence, herding, mental accounting, and loss aversion on investment decision in Nepal with risk perception as a mediator variable. Approving Prospect Theory and behavioral finance literature, the study used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze responses of 420 financial professionals. The findings revealed that while herding is positively influenced with regard to investment decisions, overconfidence, loss aversion and mental accounting found strong negative influences. Furthermore, risk perception has a strong mediating effect between behavior variables and investment decisions, attesting to its crucial role in determining financial judgment. The model showed good descriptive and predictive capacities, as reflected in high R² and Q² predict values. The study provides good insight to the growing literature on behavioral finance in developing markets and offers practical implications for investor education and strategy making in Nepal.